PENERAPAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI GOOD AGRICULTURE PRACTICES (GAP) USAHATANI KOPI RAKYAT DI LERENG ARGOPURO KABUPATEN JEMBER - Abdul Wakhid; Luh Putu Suciati (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2020)
Aplication is expected to be effort to improve coffee farming in Panti District, Jember Regency is by implementing the people's coffee farming according to Good Agriculture Practices (GAP) guidelines. This study aims to determine the level of application of Good Agriculture Practices (GAP) of people's coffee farming, and determine the factors that influence. The analysis uses scoring analysis and multiple linear regression. The results showed 1) the level of application of Good Agriculture Practices (GAP) of coffee farming was 80.58 or suitable category 2) Adj R-Square value of 63.5%, variability in the level application of Good Agriculture Practices (GAP) of people's coffee farming explain by age, education level, family dependent, land area, intensity of smallholder, access farm information, and price perception. F test results obtained that all independent variables simultan have a significant effect on the level of implementation of Good Agriculture Practices (GAP) of people's coffee farming. T test results show that the dependents of the family, land area, access to farming information, and perception of coffee prices partially have a significant effect while the age, education level, and intensity of farmers' presence partially do not significantly influence the level of implementation of Good Agriculture Practices (GAP) of coffee farming people.